2001
DOI: 10.1515/ijsl.2001.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of social context, intimacy, and distance in the choice of forms of address

Abstract: The main objective of the present study is to investigate the impact of social context as well as intimacy and distance on the choice of forms of address in Persian. However, as secondary objective, variation in the use of address forms according to social characteristics of the speakers will also be studied. The hypothesis is that variations in the forms of address are related not only to age, sex, and social class characteristics of the interlocutors but also to the setting, intimacy, and social distance. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“…Such words reflect social norms: choice of address forms depends upon social variables such as age, gender difference, formality of settings and social distance or familiarity between a pair of speakers. Forms of address are inextricably linked to politeness, i.e., the presentation of self in communication and the negotiation of face (Ervin-Tripp 1972;Keshavarz 2001;Mühlhäusler and Harré 1990). In French, the choice of pronoun of address is linked to the dimensions of power and distance and thus contributes to the realization of face systems: tu (second person singular, informal) or vous (second person plural or singular, formal).…”
Section: Introductionmentioning
confidence: 99%
“…Such words reflect social norms: choice of address forms depends upon social variables such as age, gender difference, formality of settings and social distance or familiarity between a pair of speakers. Forms of address are inextricably linked to politeness, i.e., the presentation of self in communication and the negotiation of face (Ervin-Tripp 1972;Keshavarz 2001;Mühlhäusler and Harré 1990). In French, the choice of pronoun of address is linked to the dimensions of power and distance and thus contributes to the realization of face systems: tu (second person singular, informal) or vous (second person plural or singular, formal).…”
Section: Introductionmentioning
confidence: 99%
“…The functions may include, among others, the usage of AFs to attract the addressee"s attention (Keshavarz, 2001) and employing an AF to appeal directly to the addressee (Taavitsainen & Jucker, 2003). AFs may also reflect social information about identity, gender, age, status and complex relationships in a speech community .…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…In another study, he examined the effect of distance, intimacy and social context on Persian address forms and pronominal selection. He concluded that there is a negative relation between formality of context and using intimate address terms (Keshavarz 2001). Akbari (2002) tried to classify, compare and contrast politeness strategies of Persian mono-lingual speakers in particular conditions with those employed in English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Keshavarz (2001) many researchers in the field of sociolinguistics, believe that address terms evidently show the relationship between language and society. These terms can represent politeness in speaking as well as writing.…”
Section: Theoretical Frameworkmentioning
confidence: 99%